Love-Based Curriculum as a Humanistic Approach to Realizing Inclusive Learning - Putri Rizqiyah Rahmawati; Subar Junanto; Latifah Permatasari Fajrin (CV. Edujavare Publishing, 2026)
This study explores learning strategies for early childhood education in remote and coastal areas, focusing on how contextual, community-based, outdoor, and technology-supported approaches can improve the quality of learning for young children in geographically isolated regions. Using a qualitative literature review method, this research analyzes scholarly articles, journals, and academic publications related to early childhood education practices in rural, remote, and coastal contexts published between 2020 and 2025. The findings indicate that contextual and community-based learning strategies, which integrate local wisdom and involve active participation from families and community members, significantly enhance children’s engagement, cultural identity, and developmental outcomes. In addition, outdoor learning in natural coastal environments provides meaningful experiential learning opportunities that support cognitive, physical, and socio-emotional development while fostering environmental awareness. Furthermore, technology integration serves as a complementary strategy to overcome geographical barriers by improving access to learning resources and supporting teacher professional development, although challenges such as limited infrastructure and digital literacy remain. The study concludes that a blended approach combining local-context learning, nature-based education, and digital innovation is essential to ensuring equitable and high-quality early childhood education in remote and coastal areas, while also promoting sustainable educational development.